Synthesis of Hetaryl-Substituted Benzoxazoles via Oxidative Cyclization of Phenolic Schiff's Bases - Ozokan, Kadri G.; Gumus, Mustafa K.; Kahan, Seniz (WILEY, 2008)
2-(1H-Pyrrol-2-yl)benzo[d]oxazoles, 4-(benzo[d]oxazol-2-yl)quinoline and 2-(benzo[d]oxazol-2-yl)4,6-dimethylquinolines were obtained in good yield by the oxidative intramolecular ring closing reactions of phenolic Schiff's bases with the effect of manganese triacetate.
Keywords: ELECTROCHEMICAL SYNTHESIS; CRYSTAL-STRUCTURE; 2-ARYLBENZOXAZOLES; BENZOTHIAZOLES; CONDENSATION; HETEROCYCLES; COMPLEX; IONS; DYES; Chemistry